Altruisme, Solidaritas dan Kebijakan Sosial - Robet, Robertus (UI Scholars Hub, 2013)
This essay tries to re-conceptualized altruism as sociological idea. It argues that altruism is possible. As a moral action altruism could also be operationalized to provide a ground of social policy and a tool to shape certain form of society